2022
DOI: 10.3390/nu14081591
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease and Reproductive Health: From Fertility to Pregnancy—A Narrative Review

Abstract: Despite the fact that knowledge on obstetrical management of Inflammatory Bowel Diseases (IBDs) has greatly improved over the years, many patients still actively avoid pregnancy for fear of adverse maternal or neonatal outcomes, of adverse effects of pregnancy on the disease activity, of eventual IBD inheritance, or of an increased risk of congenital malformations. Indeed, though data prove that fertility is hardly affected by the disease, a reduced birth rate is nevertheless observed in patients with IBD. Mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 94 publications
0
11
0
3
Order By: Relevance
“…In contrast, the autoimmune protocol diet (AID) had a higher subclinical response rate and a lower relapse rate than the control group, which may have been due to changes in the AID group's metabolome and microbiome that reduced inflammation [5]. According to another study, adhering to a strict diet that includes fruits, vegetables, and whole grains while limiting red meat, processed foods, and dairy products can help reduce symptoms and improve the quality of life in patients with UC [35][36][37]. Many IBD patients believe that their diet causes flare-ups and avoid their favorite foods as a result.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the autoimmune protocol diet (AID) had a higher subclinical response rate and a lower relapse rate than the control group, which may have been due to changes in the AID group's metabolome and microbiome that reduced inflammation [5]. According to another study, adhering to a strict diet that includes fruits, vegetables, and whole grains while limiting red meat, processed foods, and dairy products can help reduce symptoms and improve the quality of life in patients with UC [35][36][37]. Many IBD patients believe that their diet causes flare-ups and avoid their favorite foods as a result.…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota dysbiosis and inflammation in the colonic epithelium are related to gut leak, which damages the integrity of the intestinal barrier and leads to microbes and bacterial metabolites entering host circulation, inducing infections and diseases [ 85 ] ( Figure 1B ). For example, several studies have indicated that the fertility of women may be impaired when they suffer from inflammatory bowel disease (IBD) [ 89 ]. Other studies have also observed a higher risk of pregnancy complications such as spontaneous abortion and preterm labor in women with gut inflammation [ 90 ], suggesting an immune interaction between gut and FRT ( Figure 1C ).…”
Section: Impact Of Lifestyle On Gut Microbiome and Reproductive Healthmentioning
confidence: 99%
“…Therefore, most women with IBD are affected during their reproductive years, with fear, uncertainty, and poor knowledge of how the disease can impact their life. 2 , 3 The current literature reports that IBD women experience an higher prevalence of voluntary childlessness, 4 6 drug interruption immediately before or during pregnancy, 7 , 8 and a lower rate of breastfeeding compared to healthy women. 9 …”
Section: Introductionmentioning
confidence: 99%